Можливості сучасних охоронних систем - Шмидт, А. О.; Бабыченко, О. Ю. (ХНУРЕ, 2018)
The work presents the possibility of building security systems on the basis of the modern element and component base. The main advantages of security systems and the types of sensors used in them are presented. The modern security system is a flexible system of sensors and control nodes, which makes it possible to build it for the needs of a specific consumer.
Keywords: сучасні охоронні системи